Study on the Solution of Sand Slabbing in the Tailing Sand Bin of Huanggang Iron Ore Mine - Xin Zhu; Bokun Zheng; Liang Peng; Fengfeng Wu; Xuyan Yin; Yang Liu; Xin Yang (Advances in Civil Engineering)
In order to improve the tailings utilization rate and realize full tailings’ filling in Huanggang iron mine in Inner Mongolia, a flocculation settlement system was added, which resulted in silting and consolidation of tailings in sand silts. Based on this, the reason for the deposition and caking of tailings was obtained through analysis, and a set of coarse and fine tailings bin filling system was proposed. The tailings of the plant were pumped to the filling station by slurry pump. Firstly, the tailings with large particle size difference were divided into coarse tailings and fine tailings by hydrocyclone so that the fine tailings entered the No. 1 sand bin and the coarse tailings entered the No. 2 sand bin. Then, flocculant was added by automatic flocculant dosing device to flocculate and settle the coarse and fine tailings, and then, it was mixed, stirred, and filled into the well. The results showed the following. (1) The particle size difference of tailings in Huanggang Iron mine increased and resulted in unstable flocs. The coarse tailings settled to the bottom of the silo before the fine tailings, and the compression time was too long, leading to the phenomenon of silting and consolidation. (2) Flocculation and settlement of coarse and fine tailings in different sand silos can avoid deposition and compaction of tailings in sand silos. (3) According to the different requirements of the concentration and ratio of the filling slurry, the proportion of coarse sand and fine sand in the filling slurry can be controlled by controlling the flow size of the coarse sand and fine sand chamber, to achieve the design of reasonable particle size composition and concentration requirements. The research results are expected to provide technical support and theoretical guidance for the construction of full tailings cemented filling system in Huanggang iron mine.